2014
DOI: 10.1093/infdis/jiu428
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Hydrogen Peroxide–Induced Stress Signaling Regulates Inflammatory Genes

Abstract: Microbial infections can induce aberrant responses in cellular stress pathways, leading to translational attenuation, metabolic restriction, and activation of oxidative stress, with detrimental effects on cell survival. Here we show that infection of human airway epithelial cells with Streptococcus pneumoniae leads to induction of endoplasmic reticulum (ER) and oxidative stress, activation of mitogen-associated protein kinase (MAPK) signaling pathways, and regulation of their respective target genes. We identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…However, it is possible that SpxB-dependent H 2 O 2 induces stress within epithelial cells that may lead to alternative, non-cytolytic death processes. For instance, it has been shown that SpxB-induced H 2 O 2 triggers genotoxicity and conserved stress responses within the epithelium [24, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that SpxB-dependent H 2 O 2 induces stress within epithelial cells that may lead to alternative, non-cytolytic death processes. For instance, it has been shown that SpxB-induced H 2 O 2 triggers genotoxicity and conserved stress responses within the epithelium [24, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…In order to restore ER homeostasis, the cell activates the UPR, leading to a decreased cap-dependent protein synthesis and an increased expression of chaperones. Several pulmonary diseases have been described to induce ER stress in epithelial cells [30,31,32]. Specifically, various chronic pulmonary diseases that are linked to chronic inflammation, including asthma, COPD, or CF, have been associated with ER stress in airway epithelium [33].…”
Section: Discussionmentioning
confidence: 99%
“…The H 2 O 2 enables bacteria to escape from macrophage phagocytosis and thus contributes to the onset of bacteremia and infectious endocarditis. Regarding S. pneumoniae, several investigations revealed that the H 2 O 2 produced by S. pneumoniae is one of the virulence factors of this species (17)(18)(19)(20)(21). H 2 O 2 contributes to pneumococcal lung and blood infections in experimental animals (17,19).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the H 2 O 2 produced by S. pneumoniae is a cytotoxic virulence factor (17)(18)(19)(20)(21). A recent study showed that pneumococcal H 2 O 2 induces the activation of stress-related cellular signaling pathways (21). We also found that streptococcal H 2 O 2 stimulates the production of cytokines, such as tumor necrosis factor alpha and interleukin-6 (15,22).…”
mentioning
confidence: 85%
See 1 more Smart Citation